Idiopathic Pulmonary Fibrosis, Today and Tomorrow: Certainties and New Therapeutic Horizons - Giacomo Giulianelli; Elisabetta Cocconcelli; Giordano Fiorentù; Nicol Bernardinello; Elisabetta Balestro; Paolo Spagnolo (Pulmonary Therapy)
Abstract Idiopathic pulmonary fibrosis (IPF) represents a clinical and therapeutic challenge characterized by progressive fibrosis and destruction of the lung architecture. The pathogenesis of IPF has been long debated; while it is generally believed that repeated lung injury and abnormal wound repair are the main pathogenetic mechanisms, clear understanding of disease development and efficacious treatment remain important unmet needs. Indeed, current standard of care (i.e., the antifibrotic drugs pirfenidone and nintedanib) can slow down lung function decline and disease progression without halting the disease. In the last 2 decades, several clinical trials in IPF have been completed mostly with negative results. Yet, unprecedented numbers of clinical trials of pharmacological interventions are currently being conducted. In this review, we summarize and critically discuss the current and future treatment landscape of IPF, with emphasis on the most promising developmental molecules.